HATI DALAM PERSPEKTIF AL-QUR`AN & HADITS - Firdaus Firdaus; Mahyuddin Barni (CV. Adiba Aisha Amira, 2023)
Qalbun or heart (Anri Saputra, Mela Rospita, Vivik Shofiah, 2019: 37) is a component in the human soul that judges the right or wrong of one's feelings, intentions, thoughts, attitudes and actions. The heart (qalbun) determines behavior where good or bad depends on the condition of the heart. The heart is interpreted by changing, reversing and replacing, while Imam Al-Ghazali is of the view that the heart is the flesh that is located on the left side of the human chest which is elongated round (heart). The purpose of this paper is to describe that the Qalbu (heart) has certain meanings, functions, potentials, types and characteristics that must be used wisely to direct humans to goodness. This paper is a literature study research. Literature study is a scientific work that contains discussion of previous research and scientific references. Literature study is related to theoretical studies and other references related to values, culture and norms that develop in social situations and scientific literature (library research). The conclusions of this paper are 1. Qalbun is a